Risk of severe maternal morbidity associated with in vitro fertilisation: a population‐based study. (27th March 2019) - Le Ray, C; Pelage, L; Seco, A; Bouvier‐Colle, M‐H; Chantry, AA; Deneux‐Tharaux, C; ,
Abstract : Objective: To investigate the association between in vitro fertilisation IVF and severe maternal morbidity (SMM) and to explore the role of multiple pregnancy as an intermediate factor. Design: Population‐based cohort‐nested case–control study. Setting: Six French regions in 2012/13. Population: Cases were 2540 women with SMM according to the EPIMOMS definition; controls were 3651 randomly selected women who gave birth without SMM. Methods: Analysis of the associations between IVF and SMM with multivariable logistic regression models, differentiating IVF with autologous oocytes (IVF‐AO) from IVF with oocyte donation (IVF‐OD). The contribution of multiple pregnancy as an intermediate factor was assessed by path analysis. Main outcome measures: Severe maternal morbidity overall and SMM according to its main underlying causal condition and by severity (near misses). Results: The risk of SMM was significantly higher in women with IVF (adjusted OR = 2.5, 95% CI 1.8–3.3). The risk of SMM was significantly higher with IVF‐AO, for all‐cause SMM (aOR = 2.0, 95% CI 1.5–2.7), for near misses (aOR = 1.9, 95% CI 1.3–2.8), and for intra/postpartum haemorrhages (aOR = 2.3, 95% CI 1.6–3.2). The risk of SMM was significantly higher with IVF‐OD, for all‐cause SMM (aOR = 18.6, 95% CI 4.4–78.5), for near misses (aOR = 18.1, 95% CI 4.0–82.3), for SMM due to hypertensive disorders (aOR = 16.7, 95% CI 3.3–85.4) and due to intra/postpartum haemorrhages (aOR = 18.0, 95% CI 4.2–77.8). Path‐analysis estimated that 21.6% (95% CI 10.1–33.0) of the risk associated with IVF‐OD was mediated by multiple pregnancy, and 49.6% (95% CI 24.0–75.1) of the SMM risk associated with IVF‐AO. Conclusion: The risk of SMM is higher in IVF pregnancies after adjustment for confounders. Exploratory results suggest higher risks among women with IVF‐OD; however, confidence intervals were wide, so this finding needs to be confirmed. A large part of the association between IVF‐AO and SMM appears to be mediated by multiple pregnancy. Tweetable abstract: The risk of severe maternal morbidity is higher in IVF‐conceived pregnancies than in pregnancies conceived by other means. Tweetable abstract: The risk of severe maternal morbidity is higher in IVF‐conceived pregnancies than in pregnancies conceived by other means.